Modern Middle-Class Housing in Tehran : Reproduction of an Archetype: Episodes of Urbanism 1945-1979 - Habibi, Rana (Iran Studies, 2021)
"In Modern Middle-Class Housing in Tehran - Reproduction of an Archetype, Rana Habibi offers an engaging analysis of the modern urban history of Tehran during the Cold War period: 1945-1979. The book, while arguing about the institutionalism of modernity in the form of modern middle-class housing in Tehran, shows how vernacular archetypes found their way into the construction of new neighborhoods. The trajectory of ideal modernism towards popular modernism, the introduction of modern taste to traditional society through architects, while tracing the path of transnational models in local projects, are all subjects extensively expounded by Rana Habibi through engaging graphical analyses and appealing theoretical interpretations involving five modern Tehran neighborhoods"--